Serum Potassium Level in Acute Organophosphorus Poisoning and its Correlation with Severity in Patients Presenting to Emergency Room in a Tertiary Hospital - Basnet, Dinesh; Shakya, Yagya Laxmi; Gupta, Sanjay; Shah, Newton Ashish; Gupta, Bishal; Yadav, Manish (Journal of Karnali Academy of Health Sciences, 2026)
Background: Organophosphorus compounds (OPCs) are common causes of accidental and suicidal poisoning in agricultural countries like Nepal. Serum cholinesterase, used to diagnose organophosphorus poisoning (OP), is not reliable for predicting its severity. This study aimed to assess serum potassium as an alternative prognostic indicator for OP poisoning severity. Methodology: This single-centric cross-sectional study included patients presenting with OP poisoning at a tertiary care center over six months. Total 86 cases met the inclusion criteria. The Peradeniya organophosphorus poisoning (POP) scale categorized patients by severity. The association between OP poisoning severity and serum potassium level at presentation was studied. Results: Of the 86 cases, 47 (55%) were females. The mean age was 26.96 years (SD: 8.73), ranging from 18 to 65 years. Most cases, 53% (n=46), were aged 20-29 years. Chlorpyriphos (50%) + cypermethrin (5%) was the most common OP compound, used in 29% cases. Malathion (50%) was the least used, in 7% (n=6) of cases. At presentation, 36% (n=31) had hypokalemia, among which 6 had mild poisoning (POP score: 0-3), while 25 had moderate to severe case of poisoning (POP score: 4-11). The association between OP poisoning severity and hypokalemia was statistically significant (p-value <0.001, OR: 23.958, 95% CI). Conclusion: Serum potassium levels in patients presenting within 12 hours of OP poisoning significantly correlate with severity, as determined by the POP scale. Hypokalemia is prevalent in moderate to severe OP poisoning cases, with higher POP scores linked to lower serum potassium levels